MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN MATEMATIKA MELALUI PENERAPAN MODELBELAJAR MAKE -A MATCH PADA PESERTA DIDIK KELAS XII IPS 4 MAN KOTA TEGAL SEMESTER GASAL TAHUN 2018/2019 - WAHYUNINGSIH WAHYUNINGSIH (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2022)
The problem of this research is the low learning achievement of mathematics, especially in understanding the material for students in class X Social Sciences 4. To overcome this, the authors apply learning using the Make A Match Learning method for students. This study aims to improve learning achievement in Mathematics in the Trigonometry chapter. This research was carried out in class X IPS 4 MAN Tegal City for the 2018/2019 academic year with a total of 30 students consisting of 20 female students and 10 male students. The research procedure includes the following stages: (a) planning, (b) implementation of actions, (c) observation and interpretation, (d) analysis and reflection. Based on the results of the study, it can be concluded that the Make-A Match learning method can improve mathematics learning achievement for students, in this case the Trigonometry chapter. This is evident from the increase in the percentage level of classical completeness of students who have reached the Minimum Completeness Criteria (KKM), namely from the initial conditions that have been completed only 26.67%, in the first cycle which has been completed 56.67%, in cycle 2. or increased to 86.67%. ABSTRAKMasalah penelitian ini adalah rendahnya prestasi belajar matematika terutama dalam memahami materi pada peserta didik kelasX IPS 4. Untuk mengatasi hal tersebut penulis menerapkan pembelajaran menggunakan metode Pembelajaran Make A Match pada Pesertadidik. Penelitian ini bertujuan meningkatkan prestasi belajar Matematika pada bab Trigonometri. Penelitianini dilaksakan di kelas X IPS 4 MAN Kota Tegal tahun pelajaran 2018/2019 dengan jumlah peserta didik 30 terdiri dari 20 peserta didik perempuan dan 10peserta didik laki-laki.. Prosedur penelitian meliputi tahap: (a) perencanaan, (b) pelaksanaan tindakan, (c) observasi dan interprestasi, (d)analisisdan refleksi. Berdasarkan hasil penelitian, dapat disimpulkan bahwa metode Pembelajaran Make-A Match dapat meningkatkan prestasi belajar Matematika pada peserta didik dalam hal ini bab Trigonometri. Halini terbukti dari kenaikan tingkat prosentase ketuntasan klasikal peserta didik telah yang telah mencapai Kreteria Ketuntasan Minimum (KKM) yaitu dari kondisi awal yang yang sudah tuntas hanya 26,67%, pada siklus I yang sudah tuntas 56,67%, pada siklus 2.atau mengalami kenaikan menjadi 86,67 %.